Julien Chaisse (ed.), China’s International Investment Strategy: Bilateral, Regional, and Global Law and Policy, Oxford University Press, Oxford: 2019, pp. 560 (Polish Yearbook of International Law, 2021)
Since the implementation of its reforms and opening-up policies in 1978, China’s outward foreign direct investment (OFDI) has become one of the largest worldwide in terms of stock and flow. The volume of China’s OFDI reached USD 143.04 billion in 2018, which accounted for about 10% of the world’s total. by the end of 2018, the stock level had been stable at over USD 1.98 trillion, and there were about 43,000 overseas investment enterprises in over 80% of the world’s countries and regions. China also has a large network of international investment treaties; it has concluded 137 bilateral investment treaties and 16 free trade agreements, covering 24 countries and regions. In addition, by the end of 2019 about 138 countries and 30 international organizations had signed the one belt and one road cooperation document with China. China’s OFDI has formed a pattern of diversified investments with respect to both the location of their investments and investment subjects. in this context, the 2019 book under review. titled: “China’s international investment strategy: bilateral, regional, and Global law and policy” constitutes a substantial contribution to this vivid and vast subject.